The Influence of Health Education in Increasing Knowledge of Preventing Urinary Tract Infections (UTIs) in Children - Erina Anindya Putri; Siti Arifah (GLOBAL HEALTH SCIENCE GROUP, 2024)
Increasing knowledge about the prevention of urinary tract infections (UTIs) in children is very relevant to nursing. UTIs are common in children, potentially affecting their quality of life and causing significant complications if not treated or prevented properly. Health education plays a crucial role in empowering caregivers and children to adopt preventive measures. This health education aims to increase children's awareness, improve their quality of life, and reduce the incidence of urinary tract infections (UTIs). This study is a quantitative research, using a pre-experimental study with a one-group pretest posttest design. The research sample included 22 children selected based on purposive sampling. The data collected includes demographic data and pretest-posttest data. The data analysis will be displayed in distribution, frequency, and percentage formats. The results of this study showed that of the 22 respondents, the average pretest score was 5.45, which increased to 8.55 after the intervention. The results of the pretest-posttest showed an increase in knowledge with a percentage of 18.4%. Statistical analysis showed that the pretest-posttest assessment resulted in a p-value of 0.000 (< 0.05) and a t-value of -15.739. These results show a significant increase in knowledge after the health education intervention.